(untitled) (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2025)
The transformation of agricultural development in Indonesia from a household-based model to an institutional and area-based system through corporate farming represents a strategic step that deserves recognition. Although still in the pilot phase, the development of corporate farming is expected to serve as an effective instrument for improving farm performance and farmer welfare. This study aims to analyze the implementation of corporate farming and evaluate their impact on farmer performance, with a particular focus on Mesuji Regency. The research employs both quantitative and qualitative approaches, utilizing primary and secondary data sources. The findings indicate that the development of corporate farming has a positive contribution to increasing productivity, total output, and farmers’ income. Factors such as farmer capacity building, improved access to markets and production inputs, access to capital, and sustained technical assistance were found to significantly influence farm performance. These results underscore the urgency of strengthening farmer institutions through the corporate model as a strategy for inclusive and sustainable agricultural development.